Some Characteristics of Turbulence in Katabatic Winds over Mizuho Plateau, East Antarctica (Special Issue of the Proceedings of the First Symposium on Antarctic Meteorology and Glaciology) - Shun'ichi KOBAYASHI; Tamotsu ISHIDA (National Institute of Polar Research, 1979)
Wind turbulence was observed, using sonic anemometers, on a snow surface at Mizuho Station (2230 m above sea level, Lat. 70°41.9'S, Long. 44°19.9'E) and on a bare ice field near the Yamato Mountains (1700 m above sea level, Lat. 71°18'S, Long. 35゜40'E) in the Mizuho Plateau in 1973 by the party of the 14th Japanese Antarctic Research Expedition (JARE-14). Observations revealed, as to katabatic winds blowing above the two places, that the one above the latter is characterized by the presence of a hydraulic jump generated by nunataks there, resulting in a stronger turbulence than the one above the former which is stationary. Hence, a comparison is made in this paper between characteristics of turbulence and a hydraulic jump in a katabatic wind